THE IMPACT OF LOVE ATTITUDES ON MATE PREFERENCES: A STUDY ON EMERGING ADULTS - Sharma, Arpit; Mahdi, Anjum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the role of love attitudes in shaping mate preferences among 300 emerging adults aged 18–25 from urban and semi-urban India. Using Lee’s Love Styles framework, the research explores how love orientations—Agape, Eros, Storge, Pragma, Ludus, and Mania—predict preferences for traits such as kindness, attractiveness, religiosity, and intelligence. Participants completed the Love Attitudes Scale and a Mate Preference Scale. The findings reveal significant relationships between love attitudes and mate preferences. Agape and Storge predicted preferences for kindness and dependability, reflecting the importance of selflessness and companionship in fostering long-term relational stability. Eros was associated with preferences for physical attractiveness and sexuality, aligning with evolutionary theories on immediate compatibility. Pragma predicted preferences for religiosity, chastity, and status, influenced by cultural norms in collectivist societies. Agape also predicted preferences for education and intelligence, emphasizing intellectual compatibility. These results highlight the interplay of emotional orientations, cultural values, and gender dynamics in partner selection. By providing a culturally contextualized understanding of mate preferences, the study contributes to relationship counseling and personal development. Future research should explore these dynamics across diverse populations and longitudinal contexts to further validate these findings